Effects of garlic-derived lipid soluble organosulfur compounds on hematological parameters in mice. (July 2018) - Zhao, Ning; Guan, Min-Jie; Li, Ming-Jun; Zeng, Tao
Graphical abstract: Highlights: GO, DATS, and AMT treatment led to significant increase of total WBC counts. GO, DATS, and AMT resulted in a slight decrease of the RBC and hemoglobin levels. GO, DATS, and AMT had no effects on serum PLT levels. The spleen weight of GO, DATS, and AMT-treated mice were significantly increased compared with the control mice. Abstract: The effects of garlic oil (GO) and 5 lipid soluble organosulfur compounds on hematological parameters were investigated. SPF male ICR mice were treated with 100 mg/kg body weight of GO, diallyl trisulfide (DATS), diallyl disulfide (DADS), diallyl sulfide (DAS), allyl methyl trisulfide (AMT), or allyl methyl disulfide (AMD) for 4 weeks. We found that 1 and 2 weeks of GO, DATS, and AMT treatment led to significant increase of the blood white blood cell (WBC) counts and a slight decrease of the red blood cell (RBC) and hemoglobin (HGB) levels, while platelet was not affected. The spleen weight and the spleen weight/body weight ratio in mice of GO, DATS, and AMT groups were significantly increased compared with control group mice. These results suggest that DATS and AMT may be the bioactive compounds responsible for the elevation of WBC, which might be related with the increased extramedullary hematopoiesis in the spleen.